6th International Conference on Practical Applications of Computational Biology & Bioinformatics - Rocha, Miguel P.; Luscombe, Nicholas; Fdez-Riverola, Florentino; Rodríguez, Juan M. Corchado (Advances in Intelligent and Soft Computing, 2012)
The growth in the Bioinformatics and Computational Biology fields over the last few years has been remarkable.. The analysis of the datasets of Next Generation Sequencing needs new algorithms and approaches from fields such as Databases, Statistics, Data Mining, Machine Learning, Optimization, Computer Science and Artificial Intelligence. Also Systems Biology has also been emerging as an alternative to the reductionist view that dominated biological research in the last decades. This book presents the results of the  6th International Conference on Practical Applications of Computational Biology & Bioinformatics held at University of Salamanca, Spain, 28-30th March, 2012 which brought together interdisciplinary scientists that have a strong background in the biological and computational sciences.